HE-LHC final focus: flat beam parameters and energy deposition studies - Abelleira Fernandez, J; Cruz-Alaniz, E; van Riesen-Haupt, L; Seryi, A (JACoW Publishing, Geneva, Switzerland, 2018)
The High Energy LHC (HE-LHC) project is studying the feasibility of a new proton-proton collider with a beam energy of 13.5 TeV. The nominal optics features a β^{*} of 0.25 m and crab-cavities. Here we present a flat-beam optics that can be used with a non-zero crossing angle, in the absence of crab cavities. This is followed by energy deposition studies for the superconducting quadrupoles and dipole separators. The total dose in these magnets coming from the collision debris is evaluated